2017
DOI: 10.1016/j.dcn.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Using fNIRS to examine occipital and temporal responses to stimulus repetition in young infants: Evidence of selective frontal cortex involvement

Abstract: How does the developing brain respond to recent experience? Repetition suppression (RS) is a robust and well-characterized response of to recent experience found, predominantly, in the perceptual cortices of the adult brain. We use functional near-infrared spectroscopy (fNIRS) to investigate how perceptual (temporal and occipital) and frontal cortices in the infant brain respond to auditory and visual stimulus repetitions (spoken words and faces). In Experiment 1, we find strong evidence of repetition suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 58 publications
(83 reference statements)
8
54
0
Order By: Relevance
“…Additionally, infants who watched fewer than four block trials were excluded. This minimum is consistent with previous work done by Emberson, Cannon, Palmeri, Richards, and Aslin (2017) (Kersey & Emberson, 2016) as well as with other groups of researchers (e.g., Lloyd-Fox, Széplaki-Köllőd, Yin, & Csibra, 2015). Full-term infants included in analysis looked on average for 6.34 block trials (SD = 0.97, range = 5-8) while preterm infants looked on average for 6.63 blocks (SD = 0.93, range = 5-8).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, infants who watched fewer than four block trials were excluded. This minimum is consistent with previous work done by Emberson, Cannon, Palmeri, Richards, and Aslin (2017) (Kersey & Emberson, 2016) as well as with other groups of researchers (e.g., Lloyd-Fox, Széplaki-Köllőd, Yin, & Csibra, 2015). Full-term infants included in analysis looked on average for 6.34 block trials (SD = 0.97, range = 5-8) while preterm infants looked on average for 6.63 blocks (SD = 0.93, range = 5-8).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed,Emberson, Cannon, Palmeri, Richards, and Aslin (2017) used fNIRS to examine repetition suppression (a phenomenon where locally repeated presentation reduces neural responses to particular stimuli) across auditory and visual modalities. Indeed,Emberson, Cannon, Palmeri, Richards, and Aslin (2017) used fNIRS to examine repetition suppression (a phenomenon where locally repeated presentation reduces neural responses to particular stimuli) across auditory and visual modalities.…”
mentioning
confidence: 99%
“…While this experimental manipulation was originally designed to elicit visual repetition suppression, 25 a number of studies have found that visual repetition suppression is, at best, an extremely subtle effect in infants and, at worst, not present in the occipital cortex during infancy. 23 As a null effect of repetition suppression of visual stimuli in infants of this age using this protocol as a replication of previous and ongoing work, the current paper focuses on the comparison of auditory and visual stimulation in the occipital lobe rather than any differences in occipital lobe activation for the two types of visual stimulation. The auditory stimuli were always presented in auditory variable blocks (i.e., with all eight auditory stimuli presented in shuffled order).…”
Section: Methodsmentioning
confidence: 94%
“…The stimuli were selected to be clearly differentiable at a basic sensory level and have been found in previous studies to elicit robust auditory and visual responses (temporal and occipital cortex, respectively), but yet are engaging for infants and will encourage longer looking, which results in more trials for data analysis and trials with fewer motion artifacts. 23 All stimuli had a stimulus onset asynchrony of 1 s. The interstimulus interval (ISI) for visual stimuli was always. 25 s. The ISI for audio stimuli ranged from 0.2 to 0.3 s as the duration of the auditory stimuli ranged from 0.7 to 0.8 s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation